THE INTERACTION OF VISUAL PERCEPTION AND COGNITIVE PROCESSES IN TURKISH VERBAL EXPRESSIONS (TAMADDUN NURI JURNALI, 2025)
This study demonstrates the close interrelation between visual perception and cognitive processes in Turkish verbal expressions, highlighting the critical role of language as a connecting link between sensory experience and mental processing, thus ensuring effective communication.